Congenital syphilis in the skeleton of a child from Poland (Radom, 18th–19th century AD) - Tomczyk, Jacek; Mańkowska-Pliszka, Hanna; Palczewski, Piotr; Olczak-Kowalczyk, Dorota (Anthropological Review, 2015)
An incomplete skeleton of a 3-year-old child with suspected congenital syphilis was found in the Radom area of Poland. Squama frontalis and zygomatic bones are characterized by significant bone loss. Radiographic pictures show a geographic destructive lesion of a serpiginous shape surrounded by a zone of reactive osteosclerosis in the squama frontalis. The radiographic findings included a slight widening and contour irregularities of the distal humeral metaphyses. The appearance of teeth did not suggest Hutchinson teeth, but the examination of the permanent molars showed signs of mulberry molars. Two teeth were tested for the presence of mercury. Chemical analysis did not indicate mercury accumulation (enamel: 0.07 μg/g, dentine: 0.14 μg/g, bone: 0.11 μg/g). Mercury values obtained for the examined samples were similar to those that are typical of healthy teeth in today’s individuals.